2019
DOI: 10.1016/j.jvir.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Focal Laser Ablation of Prostate Cancer: Results in 120 Patients with Low- to Intermediate-Risk Disease

Abstract: Purpose: Can focal laser ablation (FLA) of the prostate preserve sexual and urinary function with low morbidity in men with low to intermediate-risk prostate cancer while providing adequate oncologic outcomes? Materials and methods: 120 patients with low to intermediate risk prostate cancer had transrectal FLA done. MRI thermometry controlled the ablation. Procedures were performed between 2013 and 2017. At 6 and 12 months, patients had clinical and MRI follow-up with biopsies of suspicious areas. Patients sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 36 publications
(65 reference statements)
4
32
0
1
Order By: Relevance
“…Oncologic outcome revealed no clinically‐significant cancer in ablated areas in 81.1% of lesions. Compared to similar studies using laser that showed no significant cancer in 60–100% of ablated areas, our results sit within that range. Our results are encouraging and confirm that focal laser ablation can be effective for Gleason 7 cancer.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Oncologic outcome revealed no clinically‐significant cancer in ablated areas in 81.1% of lesions. Compared to similar studies using laser that showed no significant cancer in 60–100% of ablated areas, our results sit within that range. Our results are encouraging and confirm that focal laser ablation can be effective for Gleason 7 cancer.…”
Section: Discussionsupporting
confidence: 79%
“…IPSS results demonstrated no significant changes in urinary symptoms for up to 18 months after ablation compared to baseline readings. This finding is consistent with other studies …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…PTT. In prostate cancer, PTT has been used only for treating focal lesions rather the whole gland (33,36,(77)(78)(79). Such lesions can be treated using 1-3 cylindrically diffusing fibers activated either simultaneously or sequentially.…”
Section: Prostate Tumorsmentioning
confidence: 99%